STABILITY OF OSUMILITE IN GRANULITE FACIES METAMORPHISM : KMAS SYSTEM AND NATURAL OCCURRENCES - アリマ, マコト; モトヨシ, ヨウイチ; シライシ, カズユキ; ARIMA, Makoto; MOTOYOSHI, Yoichi; SHIRAISHI, Kazuyuki (National Institute of Polar Research, 1990)
P(論文) The stability relation of osumilite in granulite facies rocks is evaluated in the light of the recent study of osumilite-bearing granulites in the Paradise River area, Laborador, Canada (M. ARIMA and C. F. GOWER : Geol./Mineral. Assoc. Canada, Program with Abst., 10,1987; to be publ. in J. Petrol., 1990) The mineral parageneses in the Paradise River granulites indicate that osumilite is stable at temperatures lower than those required for sapphirine-quartz stability. The P-T grid deduced from the Paradise River occurrence is in accordance with that proposed by E. S. GREW (Am. Mineral., 67,762,1982) for osumilite-sapphirine-quartz granulites in the Napier terrane, Antarctica. This conclusion is supported by high pressure experimental results in the KMAS system which suggest that osumilite is stable at temperatures lower than the univariant reaction En+Sil=Sa+Q. departmental bulletin paper